Effectiveness of Modeling Learning Strategies to improve Student Learning Outcomes - Sulasmi, Emilda (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2021)
This study aims to analyze the learning process at SMP Negeri 14 Medan. This research uses qualitative research, with a case study approach of SMP Negeri 14 Medan. Data collection techniques used in this study were observation, interviews, focus group discussions and documentation and then analyzed descriptively with descriptive analysis model. The results obtained are that the modeling learning strategy has a good impact on improving student learning outcomes, by making several figures into models who practice certain materials in the learning process, so that learning to dance starts from opening, core activities to closing. The conclusion of this research is that the modeling learning strategy designed by SMP Negeri 14 Medan, the modeling learning strategy takes into account the interests of students, the learning outcomes taught with modeling learning strategies are higher than those taught with conventional learning strategies.Â